Peningkatan Pengetahuan tentang Aromaterapi untuk Penanganan Nyeri Menstruasi pada Remaja - Wasis - Pujiati; Syamilatul Khariroh; Ernawati Ernawati; Hotmaria Julia Dolok Saribu; Umu Fadhilah (STIKES Wira Husada Yogyakarta, 2022)
Increasing knowledge about aromatherapy for menstrual pain management in adolescents. Aromatherapy is one of the non-pharmacological methods used to reduce the occurrence of menstrual pain, because long-term use of drugs can cause disturbances, especially body organs. Menstrual pain is a stabbing pain that is felt in the abdomen and this will interfere with the activities of some teenagers who are menstruating. This service activity is carried out as an effort to increase knowledge about the use of aromatherapy. Before counseling and after counseling, a questionnaire was given about knowledge of aromatherapy. The results of this activity showed 24 students (88.89%) with high knowledge after providing counseling and understanding about the benefits of aromatherapy in helping to reduce menstrual pain. The conclusion in this activity is that female students know and understand the use of aromatherapy as a non-pharmacological pain treatment.